Fingolimod synergizes and reverses K. pneumoniae resistance to colistin - Geng, Xiang; Zhang, Zhen-Dong; Li, Yu-Xi; Hao, Ruo-Chen; Yang, Ya-Jun; Liu, Xi-Wang; Li, Jian-Yong (Frontiers in Microbiology, 2024)
Klebsiella pneumoniae (K. pneumoniae) infection and the rapid spread of multi-drug resistant (MDR) bacteria pose a serious threat to global healthcare. Polymyxin E (colistin), a group of cationic antimicrobial polypeptides, is currently one of the last resort treatment options against carbapenem-resistant Gram-negative pathogens. The effectiveness of colistin has been compromised due to its intensive use. This study found that fingolimod (FLD), a natural product derivative, exhibited a significant synergistic bactericidal effect on K. pneumoniae when combined with colistin, both in vitro and in vivo. The checkerboard method was employed to assess the in vitro synergistic effect of FLD with colistin. FLD enhanced the susceptibility of bacteria to colistin and lowered effectively minimum inhibitory concentrations (MIC) when compared to colistin MIC, and the fractional inhibitory concentrations (FIC) value was less than 0.3. The time-kill curve demonstrated that the combination treatment of FLD and colistin had significant bactericidal efficacy. The in vitro concurrent administration of colistin and FLD resulted in heightening membrane permeability, compromising cell integrity, diminishing membrane fluidity, and perturbing membrane homeostasis. They also induced alterations in membrane potential, levels of reactive oxygen species, and adenosine triphosphate synthesis, ultimately culminating in bacterial death. Moreover, the combination of FLD with colistin significantly influenced fatty acid metabolism. In the mouse infection model, the survival rate of mice injected with K. pneumoniae was significantly improved to 67% and pathological damage was significantly relieved with combination treatment of FLD and colistin when compared with colistin treatment. This study highlights the potential of FLD in combining with colistin for treating infections caused by MDR isolates of K. pneumoniae.